2018
DOI: 10.7717/peerj.4445
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of Wif1 and β-catenin during development of anorectum in fetal rats with anorectal malformations

Abstract: PurposeThis study was performed to investigate the expression pattern of Wnt inhibitory factor 1 (Wif1) and β-catenin during anorectal development in normal and anorectal malformation (ARM) embryos and the possible role of Wif1 and β-catenin in the pathogenesis of ARM.MethodsARM was induced with ethylenethiourea on the 10th gestational day in rat embryos. Cesarean deliveries were performed to harvest the embryos. The expression pattern of Wif1 and β-catenin protein and mRNA was evaluated in normal rat embryos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…According to previous theoretical foundations, this may be because of the continuous downward extension of the URS during GDs 14–15, causing the gradual separation of the hindgut and the urethra. This is a dynamic and continuous process, and regardless of whether the hindgut and urethra are successfully separated, this process ends before GD16 (Qi et al 2000 ; Tang et al 2018 ). Therefore, based on the characteristic module analysis of clusters 0–4, the gene modules that showed positive correlation trends at GD14 and GD15 may be the key effector molecules that promote normal or ARM development.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous theoretical foundations, this may be because of the continuous downward extension of the URS during GDs 14–15, causing the gradual separation of the hindgut and the urethra. This is a dynamic and continuous process, and regardless of whether the hindgut and urethra are successfully separated, this process ends before GD16 (Qi et al 2000 ; Tang et al 2018 ). Therefore, based on the characteristic module analysis of clusters 0–4, the gene modules that showed positive correlation trends at GD14 and GD15 may be the key effector molecules that promote normal or ARM development.…”
Section: Discussionmentioning
confidence: 99%
“…In previous ARM-related studies, Gapdh and Actb were most commonly used as reference genes in RT-qPCR (Geng et al, 2017; Tang et al, 2018; Xiao et al, 2018). However, this study revealed that these two genes could be replaced by better candidates.…”
Section: Discussionmentioning
confidence: 99%
“…The next pathway is initiated with receptor WNT4. Several studies have shown that this pathway could inhibit the proliferation and migration of tumors (Seth and Ruiz I Altaba, 2016;Tang et al, 2018). In the WNT-signaling pathway, ligand WIF1 (signal transduction) binds with the receptor WNT4 to transmit the signal to TF ZEB1 through cascade proteins TUBA1B and TMEM39A.…”
Section: Genetic and Epigenetic Progression Mechanisms Of Early-stagementioning
confidence: 99%
“…In early-stage disease, PTK6 (hypoxic environment) binds with STAP2 to activate essential protein MAP4K1 and consequently the MAPK pathway (Fujita et al, 2014;Cho et al, 2017). WIF1 (Signal transduction) binds with WNT4 to activate the WNT signaling pathway (Seth and Ruiz I Altaba, 2016;Tang et al, 2018). MUC2 and HECTD3, modified by DNA methylation, could promote immune response, inflammation, cell cycle, and apoptosis.…”
Section: Genetic and Epigenetic Carcinogenic Mechanisms In Early-stagmentioning
confidence: 99%